“La lectura comprensiva como una estrategia para alcanzar un aprendizaje significativo en los niños de segundo y tercer año de educación general básica de la unidad educativa “Pujilí” - Calo Quisaguano, Sofia Viviana (2023)
The present research is focused on exploring the difficulties that second and third-year children present in reading comprehension, so as to identify the different needs and interests of teachers that allow them to use different strategies to understand and comprehend texts. Its objective is to recognize the importance of reading comprehension to achieve a significant learning in the teaching process. In addition, it is a fundamental skill that allows you to acquire new knowledge throughout both academic and professional life. In this way, they develop it from an early age, since it is fundamental for the human being, however, reading a text does not mean that it is understood coherently and reflectively. The applied paradigm was mixed (quantitative and qualitative), together the methods were used: bibliographic, descriptive, and field since, based from different theoretical references, observations, and descriptions of the qualities of the researched population. To demonstrate the incidence of the study variables, information, and data collection instruments were applied, such as the interview guide and the observation guide, which were addressed to the authorities, teachers, and second and third-year students who were subsequently processed and posted. The results show that there are problems regarding the comprehension of texts in the classroom, so it is important that teachers in their pedagogical practice must be prepared with innovative teaching resources that allow students to store new previous knowledge, ideas, and thoughts.